Miniatures and tensions: phenomenological reverberations in and around Kaija Saariaho's Lichtbogen (1985-86) - Sivuoja-Gunaratnam, Anne (Intersections, 2005)
The article studies miniatures in Kaija Saariaho's Lichtbogen for nine musicians and live electronics (1985-86). The research material consists of records, the score and composer's interviews and articles. Methodologically, the article is based on Gaston Bachelard 's phenomenology (The Poetics of Space) and Denis Smalley's "Spectromorphology." Miniatures are subtle spatio-temporal constellations, which require a non-global listening strategy, or an "aural magnification glass" in order to be perceived. In Saariaho's case, these miniatures are often imbued with musical tension, which reverberates across the material borders of music and texts. By working on the borderline between music and language, they challenge the notion that a hard separation exists between the purely musical and the extra-musical.